2010
DOI: 10.1016/j.jacc.2010.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Age as a Risk Factor for Stroke in Atrial Fibrillation Patients

Abstract: The prevalence of atrial fibrillation (AF) is related to age and is projected to rise exponentially as the population ages and the prevalence of cardiovascular risk factors increases. The risk of ischemic stroke is significantly increased in AF patients, and there is evidence of a graded increased risk of stroke associated with advancing age. Oral anticoagulation (OAC) is far more effective than antiplatelet agents at reducing stroke risk in patients with AF. Therefore, increasing numbers of elderly patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
117
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 211 publications
(134 citation statements)
references
References 75 publications
3
117
0
8
Order By: Relevance
“…25 One possible explanation may be the concerns about a higher risk of OAC-associated hemorrhage in the elderly population. 26 However, observational studies and meta-analyses 27,28 show comparable rates of major bleeding with warfarin and aspirin, whereas stroke risk is significantly reduced with warfarin in patients with AF aged >75 years. The observation that persistent AF patients were more likely to have OAC has been seen in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…25 One possible explanation may be the concerns about a higher risk of OAC-associated hemorrhage in the elderly population. 26 However, observational studies and meta-analyses 27,28 show comparable rates of major bleeding with warfarin and aspirin, whereas stroke risk is significantly reduced with warfarin in patients with AF aged >75 years. The observation that persistent AF patients were more likely to have OAC has been seen in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…leczenia AF jako metoda terapii pacjentów z objawowym, opornym na leczenie przetrwałym AF lub AF po ablacji w celu zmniejszenia objawów IIa C [808,832] Operacja labiryntowania, najlepiej obejmująca oba przedsionki, powinna być rozważana w celu zmniejszenia objawów przypisywanych AF u pacjentów poddawanych operacji kardiochirurgicznej, z uwzględnieniem dodatkowego ryzyka zabiegowego i korzyści z leczenia w celu kontroli rytmu serca [362] prób klinicznych z użyciem NOAC [39] oraz analiz przeprowadzonych u starszych Amerykanów (Medicare) [396]. Pacjenci w podeszłym wieku z AF są bardziej zagrożeni udarem mózgu, a wiec prawdopodobieństwo korzyści z OAC jest u nich większe niż u młodszych pacjentów [841], a mimo to OAC jest wciąż niedostatecznie wykorzystywane u osób w podeszłym wieku [220,842]. Mimo że w odniesieniu do innych metod leczenia stosowanych w AF uzyskano mniej dowodów, to dostępne dane przemawiają za stosowaniem dostępnych interwencji wykorzystywanych do kontroli częstości rytmu komór i rytmu serca, włącznie ze stymulatorami i ablacją przezcewnikową, bez uzasadnienia różnicowania leczenia zależnie od wieku.…”
Section: ]unclassified
“…Because stroke risk increases with age, there is a potential greater net clinical benefit of OAC among elderly patients. 21,22 Several studies investigating the risk of stroke in AF patients have found women to be at higher risk than men. [23][24][25][26][27] Two recently published large registry-based studies 25,26 on nonanticoagulated patients found a significantly higher risk of stroke overall for women of 18% and 14%, respectively.…”
Section: May 2013mentioning
confidence: 99%